EXPLORING CODE-CROSSING: HIERARCHICAL POLITENESS IN BRITISH SOCIETY DEPICTED IN A MOVIE THE KING - Rohmahwati, Agustin; Luthfiana, Syafira; Salsabila, Syifa; Jaufillaili, Jaufillaili; Budiyanti, Setia (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study investigated of code-crossing and hierarchical politeness in 15th-century English royal courts, as depicted in the film The King (2019) by using asymmetrical communication or code-crossing by Wadji, the concept of code-crossing as language choice reflecting social status, privilege, and identity influenced by social rules, and strategy politeness by Brown & Levinson, which encompasses bald on record, negative politeness, positive politeness, and off-record strategies. This research aims to analyze how these linguistic phenomena manifest within the film's social dynamics. Employing a descriptive-qualitative research method with thematical analysis, which focuses on describing and explaining topics. The data is obtained from the dialogue in the movie script explore how social status and age influence language use. The result show lower and middle class (inferior) prefer to address the upper class (superior) in high code as a sign of respect whereas the upper class frequently use low code, furthermore the result of hierarchical politeness reveal that bald on record and negative politeness strategies are mostly used. These results underscore how communication practices are shaped by social hierarchies, consistent with the continued relevance of politeness in social interactions. This research contributes to the field of sociolinguistics by empirically demonstrating the interplay of code-crossing and politeness theory in historical film context.